Hybrid repair of extensive thoracic aortic aneurysms. (30th July 2020) - Piffaretti, Gabriele; Trimarchi, Santi; Gelpi, Guido; Romagnoni, Claudia; Ferrarese, Sandro; Tozzi, Matteo; Bush, Ruth L; Lomazzi, Chiara
Abstract : Repair of an extensive thoracic aortic aneurysm (ETAA), or 'mega-aorta' syndrome, represents a surgical challenge both technically and in postoperative management. Abstract: OBJECTIVES: Our goal was to report the midterm results of hybrid treatment of extensive thoracic aortic aneurysm (ETAA) with the completion of thoracic endovascular aortic repair after proximal ascending-arch graft replacement. METHODS: This was a multicentre, observational study. Data were collected prospectively between January 2002 and March 2019 and analysed retrospectively. Inclusion criteria for the final analysis were the treatment of elective or urgent ETAA performed in a single-stage or a planned two-stage approach. Early and late survival rates were the primary outcomes. RESULTS: Indications for repair were degenerative ETAA in 27 (64.3%) patients and dissection-related ETAA in 15 (35.7%). The mean aortic diameter was 68 ± 16 mm (interquartile range 60–75). Five (11.9%) patients had a single-stage repair; and 37 underwent a two-stage approach. Three (7.1%) patients died in-hospital. The median follow-up was 49 months (range 0–204). During the follow-up period, 4 (9.5%) patients underwent aortic reintervention after a median of 32 months; however, no aortic rupture of the treated segment occurred. Overall, the estimated survival rate was 85% ± 6% [95% confidence interval (CI) 70.8–93] at 12 and 36 months and 69.5% ± 9% (95% CI 49.7–84) at 60 months. CONCLUSIONS: Hybrid repair of ETAA had satisfactory early results in this cohort of patients. At the midterm follow-up, the aneurysm-related mortality rate was acceptable with the reconstruction proving to be durable and safe with few distal aortic events.